An improved performance of PV‐fed IVC induction motor drive using clamping sequence duty ratio control. (20th August 2021) - Narendra, Ankireddy; Naik N, Venkataramana; Panda, Anup Kumar; Tiwary, Nishit
Summary: This article discloses a clamping sequence duty ratio control (CSEQ‐DRC) for photovoltaic (PV)‐fed indirect vector control (IVC) of induction motor (IM) drive. Solar PV is one of the prominent renewable green energy resources and made a pollution‐free power generation without carbon emission. The PV‐fed IM drives are used in many applications such as water pumping, electric vehicle, industrial applications, etc. However, solar panels suffer from low efficiency. Moreover, it can be overcome using the maximum power point tracking (MPPT) technique, and the MPPT is achieved using incremental conductance (Inc‐Cond). The speed of IM can be controlled using IVC with the help of an inverter. The inverter is inherently controlled based on the pulse width modulation (PWM) techniques for reducing the voltage or current harmonics. Here, the proposed CSEQ‐DRC involves two switching sequences such as CSEQ0 and CSEQ1, in every sector region. For every sector region, the appropriate sequence can be operated/selected in the less area of root mean square (RMS) of the stator flux ripples (SFRs) to reduce the line voltage/current profiles of the IM. Consequently, the torque ripples and speed fluctuations are further reduced significantly with the proposed CSEQ‐DRC than the conventional space vector duty ratio control (CSVDRC). In real‐time applications of PV‐fed IVC IM, the interface of the DSPACE DS‐1104 controller is used here to implement for both the proposed CSEQ‐DRC and CSVDRC techniques. Also, the overall performance of the IM drive is improved with the proposed technique as compared to the CSVDRC at different operating conditions. Abstract : A clamping sequence duty ratio control (CSEQ‐DRC) for photovoltaic fed indirect vector control (IVC) of induction motor (IM) drive. The speed of IM can be controlled using IVC with the help of an inverter. Here, the proposed CSEQ‐DRC reduce the line voltage/current profiles of the IM as compared to the conventional space vector control.